Age‐related changes to the satellite cell niche are associated with reduced activation following exercise. Issue 7 (28th May 2020) - Nederveen, Joshua P.; Joanisse, Sophie; Thomas, Aaron C. Q.; Snijders, Tim; Manta, Katherine; Bell, Kirsten E.; Phillips, Stuart M.; Kumbhare, Dinesh; Parise, Gianni
Abstract: Skeletal muscle satellite cell (SC) function and responsiveness is regulated, in part, through interactions within the niche, in which they reside. Evidence suggests that structural changes occur in the SC niche as a function of aging. In the present study, we investigated the impact of aging on SC niche properties. Muscle biopsies were obtained from the vastus lateralis of healthy young (YM; 21 ± 1 yr; n = 10) and older men (OM; 68 ± 1 yr; n = 16) at rest. A separate group of OM performed a single bout of resistance exercise and additional muscle biopsies were taken 24 and 48 hours post‐exercise; this was performed before and following 12 wks of combined exercise training (OM‐Ex; 73 ± 1; n = 24). Muscle SC niche measurements were assessed using high resolution immunofluorescent confocal microscopy. Type II SC niche laminin thickness was greater in OM (1.86 ± 0.06 µm) as compared to YM (1.55 ± 0.09 µm, P  < .05). The percentage of type II‐associated SC that were completely surrounded by laminin was greater in OM (13.6%±4.2%) as compared to YM (3.5%±1.5%; P  < .05). In non‐surrounded SC, the proportion of active MyoD + /Pax7 + SC were higher compared to surrounded SC ( P  < .05) following a single bout of exercise. This "incarceration" of the SC niche by laminin appears with aging and may inhibit SC activation in response to exercise.